2016
DOI: 10.19071/ripb.2016.v6.3079
|View full text |Cite
|
Sign up to set email alerts
|

Roles of plant growth substance in callus induction of Achyranthes bidentata

Abstract: In this research, callus from leaves, petioles and stems of Achyranthes bidentata was evidently initiated by plant growth substance, in which 2,4-dichlorophenoxyacetic acid (2,4-D) was very important to callus induction, but effects of other plant growth substances were various, and the optimum combination of plant growth substances for callus induction from leaves, petioles and stems was respectively obtained. Compared with callus induction from leaves and petioles, callus induction from stems was easier, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Tsatsai [ 37 ] but in contrast to the majority of previous studies which found proper exogenous auxin promotes rooting of in vitro shoots [ 35 ]. It is commonly accepted that exogenous auxin plays a key role for plant callus induction and proliferation, however, exogenous cytokinin, may play a coordinating role for callus induction and proliferation [ 35 , 38 ]. In addition, proliferation of habituated Arabidopsis callus is dependent on exogenous auxin but not on cytokinin [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tsatsai [ 37 ] but in contrast to the majority of previous studies which found proper exogenous auxin promotes rooting of in vitro shoots [ 35 ]. It is commonly accepted that exogenous auxin plays a key role for plant callus induction and proliferation, however, exogenous cytokinin, may play a coordinating role for callus induction and proliferation [ 35 , 38 ]. In addition, proliferation of habituated Arabidopsis callus is dependent on exogenous auxin but not on cytokinin [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bud formation from callus was highly influenced by auxins 2,4-D, NAA and IBA. The effect of 2,4-D was also significant for root induction (Duan et al 2012 ). The aim of the studies carried out by Sen et al ( 2014 ) was to regenerate the plantlets of A. aspera via indirect organogenesis.…”
Section: Ecdysteroid Production In Plant In Vitro Culturesmentioning
confidence: 99%